2011
DOI: 10.4103/0301-4738.73706
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of the foveal avascular zone using the Heidelberg retinal angiogram-2 in normal eyes

Abstract: Purpose:The purpose was to study the dimensions of the foveal avascular zone (FAZ) using Heidelberg Retinal Angiogram-2 (HRA-2; Heidelberg Engineering GmBH, Dossenheim, Germany).Materials and Methods:An observational study of the FAZ area and circumference was done with fundus fluorescein angiography (FFA) using HRA-2 in 31 normal individuals. The FAZ was studied using both contrast-adjusted and nonadjusted methods. Contrast adjustment was done to obtain better visualization of the finer capillaries around the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 3 publications
3
19
0
Order By: Relevance
“…Recently, John et al 18 hypothesised that the use of the contrast-adjusted method could be a better tool for studying digital angiogram pictures. They found that the FAZ area outlined by the conventional method was larger than by the contrast-adjusted method (0.6241±0.177 mm 2 vs 0.2753±0.074 mm 2 , respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, John et al 18 hypothesised that the use of the contrast-adjusted method could be a better tool for studying digital angiogram pictures. They found that the FAZ area outlined by the conventional method was larger than by the contrast-adjusted method (0.6241±0.177 mm 2 vs 0.2753±0.074 mm 2 , respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Its size as measured by fluorescein angiography reflects the status of the microcapillary circulation in the foveal area. [29][30][31][32] Also, the FAZ area has a strong positive correlation with the degree of capillary nonperfusion in diabetic retinopathies. 33,34 We observed that the FAZ area was larger (P < 0.001) in the DCP than in the SCP.…”
Section: Foveal Avascular Zonementioning
confidence: 93%
“…Various methods including histology, immunohistochemistry, fluorescein angiography (FA), and indocyanine green angiography (ICGA) have been used to evaluate the retinal vasculature 1 . Such in vivo and in vitro assessments show variations in the dimensions of the FAZ in normal eyes 2,3 . An accurate and reliable method of measuring FAZ dimensions could serve an important role in the diagnosis and management of various retinal vascular diseases that affect the FAZ, such as diabetic retinopathy or retinal vein occlusions.…”
Section: Introductionmentioning
confidence: 93%